24.0k views
4 votes
Solve for x
(-4/3) x - 6 = -26

A. −27
B. −15
C. 15
D. 27

User Nikratio
by
6.0k points

2 Answers

3 votes
The answer would be C. I found this out by adding 6 to the -6 and the -26. Then you divide -4/3 by -20 which is 15. Hope this helps! :)
User Erin Call
by
6.0k points
0 votes

- (4)/(3) x - 6 = -26

//Add 6 to both sides:

- (4)/(3) x = -20

//Multiply by -1 on both sides:

(4)/(3) x = 20

Multiply by 3 on both sides:

4x = 60

Divide by 4 on both sides:

x = 15

-----------------------------------------
Answer: x = 15 (Answer C)
-----------------------------------------
User Peter Sankauskas
by
5.9k points